Hubungan Postur Kerja, Lama Bekerja, dan Umur dengan Musculoskeletal Disorder (MSDs) pada Petani di Ngawi - Talitha Inas Zhafira; Salsabila Purnamasari (Yayasan Jompa Research and Development, 2026)
Musculoskeletal Disorders (MSDs) are health problems that can reduce productivity. Farmers are prone to MSDs because their work often involves non-ergonomic postures. This study employed a quantitative observational method with a total sampling technique, involving 90 respondents, to determine the relationship between work posture, working hours, and age with complaints of MSDs among farmers in Pleset Village, Pangkur District. The study variables included work posture, working hours, age, and MSD complaints. Work posture was assessed using the REBA method, while MSD complaints were measured with the Nordic Body Map Questionnaire. Data were analyzed using the Chi-Square test, with a significance level set at p<0.05. The results showed no significant relationship between age (p=0.164), duration of work (p=0.893), and standing work posture (p=0.877) with MSD complaints. However, there was a significant relationship with bending work posture (p=0.039). It can be concluded that a bent work posture affects MSD complaints, whereas age, length of employment, and standing posture do not. Therefore, to reduce the risk of MSDs, preventive measures such as muscle stretching before and after work can be implemented. Additionally, group exercises and ergonomic education can be conducted during community gatherings.